Learner Use of Holistic Language Units in Multimodal, Task-Based Synchronous Computer-Mediated Communication - Karina Collentine (Language Learning and Technology)
Second language acquisition (SLA) researchers strive to understand the language and exchanges that learners generate in synchronous computer-mediated communication (SCMC). Doughty and Long (2003) advocate replacing open-ended SCMC with task-based language teaching (TBLT) design principles. Since most task-based SCMC (TB-SCMC) research addresses an interactionist view (e.g., whether uptake occurs), we know little about holistic language units generated by learners even though research suggests that task demands make TB-SCMC communication notably different from general SCMC communication. This study documents and accounts for discourse-pragmatic and sociocultural behaviors learners exhibit in TB-SCMC. To capture a variety of such behaviors, it documents holistic language units produced by intermediate and advanced learners of Spanish during two multimodal, TB-SCMC activities. The study found that simple assertions were most prevalent (a) with dyads at the lower level of instruction and (b) when dyads had a relatively short amount of time to chat. Additionally, interpersonal, sociocultural behaviors (e.g., joking, off-task discussions) were more likely to occur (a) amongst dyads at the advanced level and (b) when they had relatively more time to chat. Implications explain how tasks might mitigate the potential processing overload that multimodal materials could incur.